Folktales as indigenous pedagogic tools for educating school children: A mixed methods study among the Nso of Cameroon - Wiysahnyuy, Lilian F.; Valentine, Ngalim Banfegha (Frontiers in Psychology, 2023)
In many low and middle-income countries, schools are sites of cross-cultural contact and conflict due to a mismatch between the learning priorities and pedagogical practices used in children’s homes and those they encounter in school. The alien nature of school as a learning context contributes to several negative outcomes. It hampers children’s acquisition of academic skills, limits their parents’ engagement in their schooling and prevents schools from benefiting from the learning resources and pedagogical practices available in the local context. To prevent this, many low and middle-income countries are considering the feasibility of incorporating local cultural activities into the school curriculum as a means of bridging the cultural divide between schools and the communities they serve. This research aims to inform these decisions through a case study of stakeholders’ views towards the integration of a specific indigenous pedagogic tool, folktales into school settings in Cameroon, Central Africa. Qualitative data were gathered from 20 teachers and 15 parents in Kumbo, the capital of the Nso Kingdom where traditional child-rearing customs remain strong. A thematic analysis of the data revealed that most parents told their children folktales as one component in an indigenous participatory pedagogy designed to stimulates some cognitive skills and enhance moral development among children. Most teachers and parents believed that there were many potential importance of integrating folktales into schools as a traditional pedagogy for schoolteachers’ professional practice. All teachers reported that they used folktales during lessons and/or pupils’ free time. Like parents, teachers both narrated folktales and invited children to narrate them though some parents indicated that it was not necessary. This pattern of findings supports the conclusion that folktales provide invaluable pedagogic values and prospects for schools and formal education in general. Caution should be exercised in any attempt to generalize these findings because the sample and the geographical site were limited. However, this study suggests that folktales may be a readily available indigenous pedagogic tool that has both a high level of acceptability among teachers and parents and can be effective in bridging the cultural divide between schools and communities in many low and middle-income countries.